Color: The Spirit of Painting - Shah, Krishna Prakash (Journal of Fine Arts Campus, 2021)
Color exists in the presence of light. Light not only brings forth the existence of color but also helps to perceive its reality. Color is a powerful medium to express our feelings, and that also evokes emotional responses which attract and keep the attention of a beholder. Color combination in painting is concerned with aesthetic aspects. The color beauty sustains the undivided attention to the beholder. Color amplifies the degree of emotion that touches and influences the human body, mind and soul directly which leads towards contemplation. The contemplation opens up the way to the journey of eternity. All this is possible through the combination of harmonious and contrastive colors that awakens a corresponding sensation, which directly works upon the soul. Therefore, color is the spirit of painting that makes the work of painting lively by putting breath into it. This article, thus, attempts to trace how color becomes the spirit of painting. Color as the spirit of painting will be the center of research focusing on the influence of color upon human beings. The main objective of this article is to study the role of color in painting. The study explains the impact and aesthetic value of color in painting. It is relevant to explore the strength of color application in painting. The qualitative model of research is adopted to analyze and interpret the artworks.